Efisiensi Pemasaran Tomat di Desa Tondegesan Kecamatan Kawangkoan Kabupaten Minahasa - Wowiling, Yozi; Dumais, Joachim Noch Karel; Jocom, Sherly Gladys (AGRI-SOSIOEKONOMI, 2023)
Tomatoes are worth cultivating and developing because they have good economic value and the demand for tomatoes continues to increase along with the widespread use of tomato plants for various purposes, both for culinary and food industries. This research was conducted from May to June 2022. The research site is located in Tondegesan Village, Kawangkoan District, and Minahasa Regency. Based on the research conducted, it can be interpreted that in marketing channel I, farmers sell tomatoes to existing traders. Traders are influenced by the number of tomatoes calculated in cash units worth Rp100 and the distance between the farmer's location and the Kinali Village. Marketing or transportation costs for one cash box are between Rp1.111 and one cash box containing approximately 20 kg. The purchase price of tomatoes from producing farmers is Rp11.000 per kg and sold to consumers Rp15.000 per kg. The traders referred to in marketing channel I are traders who travel between villages. Consumers who buy tomatoes are people in Kinali Village. In marketing channel II, farmers sell tomatoes to wholesalers then process them in packaging to be ready for sale to settlement traders outside the village of Tondegesan and sell them to the city of Manado at the Berhati market. In this process, wholesalers incur quite large marketing costs in transportation costs and packaging. Marketing or transportation costs incurred by wholesalers for one cash are between Rp985 and one cash containing approximately 20 kg. The purchase price of tomatoes from producing farmers is Rp11,000 per kg and sold to switching traders is Rp13.500 per kg with a profit of Rp1.515. So the marketing margin earned by wholesalers is Rp2.500 per kg. Then the marketing or transportation costs for one cash are Rp1.116 and one cash contains approximately 20 kg. The purchase price of tomatoes from wholesalers is Rp13.500 per kg and sold to consumers Rp15000 per kg with a profit of Rp384 per kg. Thus the marketing margin obtained by the retailer is Rp1.500 per kg.